1990
DOI: 10.1128/jvi.64.5.2260-2264.1990
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic protection induced by synthetic peptides corresponding to three serotypes of foot-and-mouth disease virus

Abstract: Synthetic peptide vaccines of the general sequence Cys-Cys(200-213)-Pro-Pro-Ser-(141-158)-Pro-Cys-Gly, where the numbered residues refer to VP1 sequences of three different strains of foot-and-mouth disease virus, have been evaluated in cattle and guinea pigs. High levels of serotype-specific (homotypic) antiviral and antipeptide antibody were produced with each peptide. The A-and 0-serotype peptides provided complete protection of guinea pigs against their respective virus challenges. The C-serotype peptide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 17 publications
0
10
1
1
Order By: Relevance
“…In this study, the use of a large number of animals provided statistically significant evidence for a lack of solid protection in bovines vaccinated with peptides representing FMDV C3 Arg85 VP1 sequences (Table 7). Thus, in spite of evidence of some homotypic and heterotypic protection by synthetic peptides in guinea pigs and cattle (25), a firm and consistent protection in bovines is not systematically achieved (35). An inactivated vaccine acceptable for use in the field must attain 80% protection in cattle (9); 90% protection was obtained with the whole-virus vaccine used as a positive vaccination control in our experiments (Tables 3 to 5).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the use of a large number of animals provided statistically significant evidence for a lack of solid protection in bovines vaccinated with peptides representing FMDV C3 Arg85 VP1 sequences (Table 7). Thus, in spite of evidence of some homotypic and heterotypic protection by synthetic peptides in guinea pigs and cattle (25), a firm and consistent protection in bovines is not systematically achieved (35). An inactivated vaccine acceptable for use in the field must attain 80% protection in cattle (9); 90% protection was obtained with the whole-virus vaccine used as a positive vaccination control in our experiments (Tables 3 to 5).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper, we addressed the question of the specificity of the response to synthetic FMD peptides and demonstrated that, contrary to expectations, each of the A, C, and 0 serotype peptides conferred heterologous as well as homologous protection of guinea pigs (8). From the available data, it was not possible to identify the sequence or sequences of each peptide responsible for heterologous protection, although it was speculated that the highly conserved R-G-D tripeptide within the 141-158 region might be involved.…”
mentioning
confidence: 84%
“…Peptides. The following peptides were synthesized by conventional solid-phase methods and purified to near homogeneity by reverse-phase chromatography as previously described (8).…”
Section: Materuils and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Krebs et al (20) have shown that swine vaccinated with peptides based on the type 0 G-H loop developed FMD following challenge, and an antigenic variant isolated from one animal was not neutralized by antipeptide sera. Vaccination-challenge studies using synthetic peptides have also failed to demonstrate complete protection in cattle, offering further evidence of failure of vaccines presenting only a single antigenic site (12,13).…”
mentioning
confidence: 99%